The Relationship Between Learning Style And Learning Independence With The Results Of Economics Learning In Xi Social Studies Class At Shs 1 Banyuke Hulu Regency Landak - Mashudi, Mashudi; Al Hidayah, Riama; Prihantari, Bunga (International Journal of Educational Research & Social Sciences, 2024)
Teachers are faced with the characteristics of various learning styles and independence of students. Not a few also experience learning difficulties in classroom learning activities. This statement is supported by an observation on April 27, 2024 conducted by researchers at Banyuke State High School. The results are that there is a varied delivery of student assignments, collecting assignments, some are fast and some are slow, the results of economic learning from the test in general answer economic material also varies. The condition is seen in the learning results that do not reach completeness. Low learning outcomes are related to students' learning style and learning independence. In addition to learning independence, the learning style factor is believed to be strongly related to learning outcomes, namely learning styles. The method used in the study is a correlational study through a quantitative research approach. The design form is correlational. The conclusions in this study are 1) the relationship between learning style and economic learning outcomes is relatively strong, 2) the positive and significant relationship between learning independence and economic learning outcomes is relatively strong, and 3) the positive and significant relationship between learning style and independence is relatively strong with economic learning outcomes. So that if the learning style and learning independence are done well, the economic learning outcomes will increase because of the seriousness of students in learning and thinking critically in doing assignments.